1976ネン カキ ナンキョク カイ インドヨウ ク ノ トウケイ 33.5゜ セン ニ ソッテ エラレタ カイアシ ルイ シリョウ - 山田, 智; ヤマダ, サトシ; 谷村, 篤; タニムラ, アツシ; 箕田, 嵩; ミノダ, タカシ; Yamada, Satoshi; Tanimura, Atsushi; Minoda, Takashi (1992)
P(論文) 1976年2月25日から3月2日の間, 南極海インド洋区の東経33.5°線に沿った南緯50°以南の6観測点において採集したカイアシ類の種組成を調査した。採集はノルパックネット(口径45cm, 目合0.33mm)を用いて水深200mから表面までの鉛直曳によって行われた。各測点ともカイアシ類が最も卓越して出現し, 動物プランクトン総個体数の85%以上を占めた。Oncaeidaeを除く14属18種類のカイアシ類が同定された。Calanus propinquus, Calanoides acutus, Rhincalanus gigas, Ctenocalanus vanus, Scolecithricella glacialisおよびOithona similisはほぼ全地点で出現した。Miclocalanus pygmaeus, Lucicutia sp., Haloptilus ocellatus, Haloptilus oxycephalusおよびMetridia gerlacheiは南緯60°以南で, Calanus simillimus, Clausocalanus laticeps, Metridia lucensおよびOithona frigidaは南緯60°以北でのみ出現した。Euchaeta antarctica, Racovitzanus antarcticusおよびHeterorhabdus austrinusは偶発的にあるいは少数が出現しただけであった。 Zooplankton samplings were conducted at 6 stations along 33.5°E in the Indian sector of the Antarctic Ocean from 25 February to 2 March in 1976 by the 17th Japanese Antarctic Research Expedition. Vertical hauls from a depth of 200m to the surface with a Norpac net (45cm in diameter, 0.33mm mesh openings) were carried out. Copepoda occupied more than 85% of the total individual numbers of zooplankton at all stations. The species composition and abundance of copepods were investigated. A total of 18 species except for Oncaeidae were identified. Calanus propinquus, Calanoides acutus, Rhincalanus gigas, Ctenocalanus vanus, Scolecithricella glacialis and Oithona similis were found commonly at almost all stations. Miclocalanus pygmaeus, Lucicutia sp., Haloptilus ocellatus, Haloptilus oxycephalus and Metridia gerlachei occurred south of 60°S and Calanus simillimus, Clausocalanus laticeps, Metridia lucens and Oithona frigida occurred north of 60°S. Euchaeta antarctica, Racovitzanus antarcticus and Heterorhabdus austrinus occurred sporadically and/or in small number. departmental bulletin paper